2011
DOI: 10.2174/156802611795589566
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Eukaryotic Type Serine-Threonine Protein Kinases: From Structural Biology to Targeted Anti-Infective Drug Design

Abstract: Signaling through protein kinases is an evolutionary conserved, widespread language of biological regulation. The eukaryotic type serine-threonine protein kinases (STPKs) found in normal human microbiote and in pathogenic bacteria play a key role in regulation of microbial survival, virulence and pathogenicity. Therefore, down-regulation of bacterial STPKs emerges as an attractive approach to cure infections. In this review we focused on actinobacterial STPKs to demonstrate that these enzymes can be used for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 88 publications
0
25
0
1
Order By: Relevance
“…Several chemical scaffolds (Vertex Pharmaceuticals Inc.) (Magnet et al 2010;Danilenko et al 2011;Lougheed et al 2011;Chapman et al 2012) 1996; Pitarque et al 2008;Dhiman et al 2011). Whether Mtb requires phosphatidylglycerol, CL, PS, and PE for growth is at present not known.…”
Section: Inner and Outer Membrane Extractable Lipidsmentioning
confidence: 99%
“…Several chemical scaffolds (Vertex Pharmaceuticals Inc.) (Magnet et al 2010;Danilenko et al 2011;Lougheed et al 2011;Chapman et al 2012) 1996; Pitarque et al 2008;Dhiman et al 2011). Whether Mtb requires phosphatidylglycerol, CL, PS, and PE for growth is at present not known.…”
Section: Inner and Outer Membrane Extractable Lipidsmentioning
confidence: 99%
“…Although bacteria primarily rely on histidine kinases and their associated regulatory responders for phosphorylation-dependent signaling, some also utilize eukaryotic-like Ser/Thr Protein Kinases (STPKs) [56]. Like eukaryotes, bacteria can use STPKs to respond to stress, but they also participate in other processes such as pathogenicity, thereby providing important drug targets [56]. The best characterized bacterium in this regard is M. tuberculosis, the causative agent of tuberculosis, which tops the charts in the prokaryotic kingdom with eleven STPKs [57].…”
Section: Phospho-epitope Independent Interactionsmentioning
confidence: 99%
“…Also, some BSTK are involved in virulence of Mycobacteria and resistance of Streptomyces to aminoglycoside antibiotics 2,3 . Since it is evident that BSTK play an indispensable role in some prokaryotic organisms, these protein kinases are considered as attractive antibacterial drug targets 1,4 . It was also shown that protein kinase inhibitors of eukaryotic serine/threonine protein kinase(s) (ESTK) could be active against some BSTK 1,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Since it is evident that BSTK play an indispensable role in some prokaryotic organisms, these protein kinases are considered as attractive antibacterial drug targets 1,4 . It was also shown that protein kinase inhibitors of eukaryotic serine/threonine protein kinase(s) (ESTK) could be active against some BSTK 1,4,5 . Several years ago, we have synthesized a combinatorial library of compounds to find inhibitors of ESTK 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation